A Pencil Shaped Switched Capacitor Multilevel Inverter with Voltage Boosting Ability - Meraj, S.T. (Institute of Electrical and Electronics Engineers Inc., 2021)
This manuscript proposes a unique topology of switched capacitor based multilevel inverter (MLI) that employs capacitors and DC sources as DC connections to generate staircase voltage waveforms. The use of DC sources is reduced in this MLI. Even with lower DC sources, the MLI is capable of generating 9 voltage levels. The novel MLI module produces 9 levels with a pair of equal DC sources. Two chargeable capacitors and 12 semiconductor switches are also included in this module. The capacitors are self-charging and they do not need any additional circuit. Because of the low number of components, it is suitable for a wide variety of applications. The module is developed using the combination of a directional inverter, a T-type inverter, and a few additional switches. It can also be extended by utilizing a cascade modular configuration, resulting in a module that can produce higher voltage levels. In the absence of any external circuit like H-bridge circuit, this new module can still synthesize negative voltage steps. In order to obtain an output voltage which is almost sinusoidal, the nearest level control switching modulation (NLC) scheme is used. Simulations are conducted using MATLAB/Simulink, and a hardware model is developed to demonstrate the MLI's simulation and experimental performance. Â© 2021 IEEE.